PENGARUH PEMBERIAN HORMON NAA, PUPUK GANDASIL DAN PUPUK GROWMORE PADA PERTUMBUHAN TANAMAN ANGGREK - Astri Sumiati; Astutik Astutik (BUANA SAINS, 2019)
Orchid is an ornamental plant, including the Orchidaceae tribe, which is widely favored among the ornamental plant community because it has high economic value, unique shapes, attractive colors and longer-lasting blooming flowers, one of which is a Phalaenopsis orchid. One of the efforts to accelerate the vegetative phalaenopsis can be done with the application of the NAA hormone and leaf fertilizers such as Gandasil fertilizer and Growmore fertilizer. The aims of this research to determine the effect of NAA, Gandasil and Growmore fertilizer types on the growth of hybrid Phalaenopsis orchids. The study was conducted at Greenhouse Jalan Tlogomas Kec. Lowokwaru, Malang City, for 5 months. The experiment was carried out using a factorial Completely Randomized Design (CRD) consisting of 2 factors namely, the factor I: NAA concentration: control 0 ppm (N0), 100 ppm (N1), 200 ppm (N2), and 300 ppm (N3). Factor II: leaf fertilizer, Growmore (P1) and Gandasil D (P2). Variables observed included: when buds appeared, leaf length, leaf width and percentage of live plants. The results showed that there was an interaction between the concentration of NAA and the type of leaf fertilizer on the emergence of shoots. When the fastest shoots appear at 100 ppm NAA, Growmore fertilizer (N1P1), which is 29 days. The NAA hormone influences the increase in leaf length and leaf width until 16 weeks of age. The best growth of hybrid Phalaenopsis was obtained at the administration of 200 ppm NAA with an increase in leaf length of 1.49 cm and an increase in leaf width of 1.06 cm until 16 weeks of age. Growmore and Gandasil D did not affect the vegetative growth of hybrid Phalaenopsis Orchid plants.